2017
DOI: 10.1242/jeb.143966
|View full text |Cite
|
Sign up to set email alerts
|

Diel rhythms and sex differences in the locomotor activity of hawkmoths

Abstract: Circadian patterns of activity are considered ubiquitous and adaptive, and are often invoked as a mechanism for temporal niche partitioning. Yet, comparisons of rhythmic behavior in related animal species are uncommon. This is particularly true of Lepidoptera (butterflies and moths), in which studies of whole-animal patterns of behavior are far outweighed by examinations of tissue-specific molecular clocks. Here, we used a comparative approach to examine the circadian patterns of flight behavior in Manduca sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…d–f). Similar qualitative observations have been made by other field researchers (Table S1) and laboratory studies have shown that the short‐tongued hawkmoth Hyles lineata exhibits crepuscular flight rhythms (Broadhead et al ., ), in contrast to the long‐tongued hawkmoth Manduca sexta which exhibits flight activity throughout the night (Hoballah et al ., ; Broadhead et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…d–f). Similar qualitative observations have been made by other field researchers (Table S1) and laboratory studies have shown that the short‐tongued hawkmoth Hyles lineata exhibits crepuscular flight rhythms (Broadhead et al ., ), in contrast to the long‐tongued hawkmoth Manduca sexta which exhibits flight activity throughout the night (Hoballah et al ., ; Broadhead et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Information on the diel activity patterns of flower‐visiting animals is essential for understanding the ecology of pollination mutualisms (Stone et al ., ; Hoballah et al ., ; Broadhead et al ., ). However, there is little verified information regarding the activity patterns of nocturnal flower‐visiting insects, such as hawkmoths, as it is notoriously difficult to observe them in a manner that does not affect their behaviour, and because human stamina for all‐night observations is limited.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…But it often fails for crepuscular species, and species that fly during the night and the day ("both"). For example, even though Manduca sexta is often considered crepuscular, one study has found it is almost entirely nocturnal when compared to Hyles lineata, which is active both during the night and day 75 .…”
Section: Diel Niche Assignmentmentioning
confidence: 99%
“…Flying animals rely on maneuverability to survive in unsteady environments whether evading predators, finding mates, or foraging for food (Dudley 2002b, Sprayberry & Daniel 2007, Broadhead et al 2017). As these animals actively move through their environments, locomotion depends on interactions between their body and the surrounding fluid to produce necessary forces and torques.…”
Section: Introductionmentioning
confidence: 99%